Building an Integrated System for Wastewater Treatment in Dairy Farm Using Algae - Khashan, Anas; Zatari, Abed alruhman; Da'na, Omar (جامعة بوليتكنك فلسطين - ميكانيك, 2020)
Dairy industry is one of the major polluting industries in Palestine and elsewhere. Locally, dairy wastewater is discharged into sewer system or open spaces without any kind of treatment causing high organic loads and septic degradation. The wastewater in dairy farms is an important problem in Palestine, where most of the wastewater is dumped into unprepared pits or in open valleys, which causes many environmental problems, for example, bad smells, harmful insects spread, groundwater pollution, and soil pollution, so This water must be used and treated to make it usable again, especially in the presence of the Israeli occupation. The project aims to design and build an integrated system for treating wastewater in dairy farms using algae. Besides that produce distilled water and biomass. Samples were taken to conduct an exhaustive compilation of dairy wastewater characterization and a comparative study between the different features of dairy wastewater, COD, pH, TDS, NO3. Distilled water has been produced around 500ml daily, piece of kink at 20 X 20 cm dimensions was take to check the volume of biomass growth because the results take days as like the features of dairy wastewater . The sample's measurement was taken four times in different days, at around 5:00 PM. Four tests were taken for each sample TDS, NO3, pH, the results as shown in the figures. The pH and NO3 readings shows positive changes during days, that's where the ratio of pH and NO3 decreased, this indicates the ability of algae to treat wastewater.
no of pages 105 , ميكانيك 9/2020
Keywords: Algae -Wastewater Treatment